Effect of Green Manure and Bio-fertilizers on the Availability of Zinc and Copper and their Uptake by Rice (Oryza sativa L.) - Sarkar, S.; Santra, G. H.; Mandal, M. (International Journal of Bio-resource and Stress Management, 2015)
An experiment was conducted at the Regional Research Technology Transfer Station (RRTS), G. Udaygiri, Phulbani and Odisha during kharif 2001 and 2002, using rice cultivar khandagiri. The objectives of the study was to evaluate the effects of different green manures (GM) (Sesbania aculeata, Gliricidia leaf and Lantana camera), bio-fertilizers (Azospirillum) with and without inorganic fertilizers (30 and 60 kg N ha-1) on productivity, availability of zinc (Zn) and copper (Cu) and their uptake by rice (Oryza sativa L.). The experiment was laid out in RBD replicated thrice with eleven treatments. The results of the experiment showed that the periodical changes in available Zn and Cu contents in soil recorded highest in the treatments T9 (50% recommended N+50% N through dhaincha) with the simultaneous highest uptake of Zn and Cu by rice grain and straw. The combined effects of N fertilizers and dhaincha on 50:50 basis gave highest plant height, effective tillers hill-1, panicle length, grains panicle-1 and test weight in T9 treatments. The highest rice yield (3.31 t ha-1) was recorded in the same treatment T9 which was at par with the treatments T10 (3.28 t ha-1) and T11 (3.22 t ha-1) that received GM as gliricidia leaf and Lantana camera respectively along with 50% inorganic N. The effect of different GM+urea on rice yield was in order of dhaincha>gliricidia>Lantana camera.